Experiences of schizophrenia patients with treatment buddy support during the COVID-19 pandemic - Nomhle Mvunelo; Firoza Haffejee; Yasmeen Thandar (AOSIS, 2024)
Background: Schizophrenia is a major psychiatric disorder affecting physical, psychosocial, and cognitive functioning. Treatment includes pharmacological and psychotherapeutic interventions. Adherence to prescribed medication is critical but reportedly low, because of side effects, failure to understand instructions, a lack of insight about the condition, cognitive deficits, and financial difficulties. Interventions to promote adherence to medication are required. This study introduced a treatment buddy to provide the patient with virtual support in adherence to medication. Aim: The aim of this study was to explore the participants' lived experiences of a treatment buddy support. Setting: A specialised psychiatric clinic in a resource-constrained district of KwaZulu-Natal, South Africa. Methods: A qualitative study design, using semi-structured one-on-one interviews, was used to collect in-depth data from 24 participants, suffering from schizophrenia and who had been offered virtual treatment buddy support for 6 months. Data were analysed using thematic analysis. Results: The intervention improved adherence to medication. Participants indicated that the text messages served as reminders to take their medication daily. An alleviation of associated problems such as sleeping difficulties was observed. Participants were willing to encourage other patients suffering from schizophrenia to join 'treatment buddy services'. Conclusion: The virtual treatment buddy support increased awareness of the importance to adhere to antipsychotic medications among patients suffering from schizophrenia and helped to resolve other schizophrenia-related problems experienced by the participants. Contribution: The study has provided a supportive intervention that can be utilised by mental health institutions to address poor adherence to medication by patients suffering from schizophrenia.